Transformasi Sosial dalam Pendidikan Islam Perspektif Hadis - Mela, Lita (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Social Transformation in Islamic Education Perspective of Hadith The social transformation that has a bad or good impact affects various aspects, one of which is the aspect of Islamic education. In Islamic education, the social transformation will occur in harmony with the progress of the world and the development of science. Social transformation can have a positive impact such as digital learning media, hybrid learning models, and a negative impact such as student moral deviation, promiscuity, and hoax news, that are not in accordance with hadith’s perspective. This study will answer all social transformations that occur in Islamic education, both in the form of social transformations that have good impacts and bad impacts, This research applies a curative methodology with a type of literature study sourced from books, journals, and hadith. The results showed that the hadith perspective regarding the development of science or social transformation has a positive impact on the world of education, on Sahih Muslim, Number. 4356 and Number. 3084, Chapter: The Problem of Religion taught by the Messenger of Allah and the difference between religious affairs and his opinion in matters of the world. The hadith perspective on social transformation that has a bad impact on the world of education, in the Hadith of Tirmidzi, Number 2431, BAB: others.